Declining valuations and equilibrium bidding in central bank refinancing operations - Christian Ewerhart; Nuno Cassola; Natacha Valla (European Central Bank (ECB), 2006)
It is argued that bidders in liquidity-providing central bank operations should typically possess declining marginal valuations. Based on this hypothesis, we construct an equilibrium in central bank refinancing operations organised as variable rate tenders. In the case of the discriminatory pricing rule, bid shading does not disappear in large populations. The predictions of the model are shown to be consistent with the data for the euro area.
Keywords: D44; E52; 330; discriminatory auction; Eurosystem; Open market operations; uniform price auction; Offenmarktpolitik; Auktion; Refinanzierung; Zentralbank; Eurozone; EU-Staaten; Theorie